2020
DOI: 10.3892/etm.2020.8494
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant treatments for resectable rectal cancer: A network meta‑analysis

Abstract: Different neoadjuvant therapy regimens are available for rectal cancer, but the relative effects are controversial. The aim of the present network meta-analysis (NMA) was to estimate the relative efficacy and safety of neoadjuvant therapies for resectable rectal cancer. MEDLINE, EMBASE and Cochrane Central Registry of Controlled Trials were searched for publications dated from 1946 up to June 2018. The present study included randomized clinical trials that compared treatments for resected rectal cancer: Surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…North European guidelines recommend short-course radiotherapy (SCRT), 25 Gy in 5 fractions, followed by total mesorectal excision (TME) surgery for intermediate risk rectal cancer [1][2][3]. The addition of SCRT to TME surgery in this patient group reduces the risk of local recurrences compared to TME surgery alone [3,4]. In addition, the Stockholm III trial showed fewer postoperative complications after a prolonged interval between SCRT and TME compared to direct surgery after SCRT [5].…”
mentioning
confidence: 99%
“…North European guidelines recommend short-course radiotherapy (SCRT), 25 Gy in 5 fractions, followed by total mesorectal excision (TME) surgery for intermediate risk rectal cancer [1][2][3]. The addition of SCRT to TME surgery in this patient group reduces the risk of local recurrences compared to TME surgery alone [3,4]. In addition, the Stockholm III trial showed fewer postoperative complications after a prolonged interval between SCRT and TME compared to direct surgery after SCRT [5].…”
mentioning
confidence: 99%
“…This outcome may indicate that the local control power of NAC without radiotherapy may be insufficient. In fact, Zhong et al reported that NACRT was more effective than NAC in terms of local recurrence [24]. However, the histopathological characteristics of the patients with R1 operation were poorly differentiated adenocarcinoma (por) in two of the three patients and mucinous adenocarcinoma (muc) in one of the three patients.…”
Section: Discussionmentioning
confidence: 97%
“…Because the exact relationship between PLR and the OS and DFS of patients receiving NAC is yet unknown, we conducted a meta-analysis to determine the relevant relationships. In some cases, the addition of NAC resulted in greater tumor downsizing and increasing the rate of complete resection, improved the pCR rate, and demonstrated local control, but the relative effects are controversial [38–45] . To the best of our knowledge, meta-analyses are a more comprehensive update that systematically and quantitatively evaluates this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the addition of NAC resulted in greater tumor downsizing and increasing the rate of complete resection, improved the pCR rate, and demonstrated local control, but the relative effects are controversial. [38][39][40][41][42][43][44][45] To the best of our knowledge, meta-analyses are a more comprehensive update that systematically and quantitatively evaluates this topic. In the present meta-analysis of 18 studies including 3653 cases, we evaluated the prognostic role of PLR in solid tumors following NAC or nCRT.…”
Section: Discussionmentioning
confidence: 99%